Estudo da capacidade de mascaramento de resinas compostas: influência do substrato e do envelhecimento - Perez, Bibiana Gabardo (2021)
The presence of teeth with severe discoloration can cause great discomfort for patients, especially when these teeth are located in the anterior region of the dental arch, leading to the search for a restorative treatment to correct this problem. The use of resin composites to mask discolored teeth is an excellent treatment, because in addition to presenting great results, it is also a minimally invasive technique. A variety of materials and techniques are available for the restorations. All of the techniques described prove to be successful, especially when a more opaque resin is used to mask the discolored substrate. There is few evidence specifically related to the technique of layering resin composites to mask discolored substrates and their behavior against aging. Thus, there is a need for additional studies, such as in vitro studies and literature reviews, to deepen knowledge on the subject and also to scientifically confirm the distinct benefits of each existing technique. Therefore, the objective of the present study is to evaluate the masking ability of resin composites, through an in vitro study and a scoping review. In the in vitro study it was possible to conclude that the masking ability was affected by the layering technique, the discolored substrate and the water aging. In the scoping review, to achieve an ideal masking of the C4 substrate, an opaque resin layer at least 0.5mm thick or a combination of resins with different degrees of translucency/opacity with a final thickness of 1.5mm must be applied. To mask the black background of the oral cavity, a layer of at least 1.0mm of opaque resin composite must be used.